2011
DOI: 10.1111/j.1440-1797.2010.01425.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of chronic nephrotoxicity of long‐term cyclosporine A treatment in adult patients with steroid‐dependent nephrotic syndrome

Abstract: Mild decrease in renal function and hypomagnesemia were found in adult SDNS patients with long-term CsA treatment. Careful monitoring of renal function, blood pressure and serum magnesium levels is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…In the present study, the levels of proteinuria decreased dramatically in the patients treated with the combined therapy, while the eGFR values increased, indicating that the role of CsA in reducing proteinuria is not limited to its effects in improving glomerular hemodynamics and reducing glomerular filtration. The biggest problem associated with CsA treatment is renal toxicity, which can result in damage to the renal function by inducing renal vasoconstriction and interstitial fibrosis (34)(35)(36). Our study showed that even though we used a medium dose of 3 mg/kg/d as the initial dose of CsA, more than 25% of the patients treated with the combined therapy showed a transient drop in eGFR, although most of them quickly returned to their previous values.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the present study, the levels of proteinuria decreased dramatically in the patients treated with the combined therapy, while the eGFR values increased, indicating that the role of CsA in reducing proteinuria is not limited to its effects in improving glomerular hemodynamics and reducing glomerular filtration. The biggest problem associated with CsA treatment is renal toxicity, which can result in damage to the renal function by inducing renal vasoconstriction and interstitial fibrosis (34)(35)(36). Our study showed that even though we used a medium dose of 3 mg/kg/d as the initial dose of CsA, more than 25% of the patients treated with the combined therapy showed a transient drop in eGFR, although most of them quickly returned to their previous values.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, CsA has an antiproteinuric effect independent of its immunosuppressive function in T cells,directly resulting from the stabilization of the podocyte actin cytoskeleton (32). Research has showed that the administration of CsA can reduce proteinuria in patients with many types of chronic glomerulonephritis and nephrotic syndrome, even those who are resistant to steroids (33,34). In our prospective, randomized, controlled trial, we showed that treatment with both full-dose corticosteroids alone and mediumdose glucocorticoids combined with CsA rapidly reduces proteinuria, even by the end of the first month of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Антипротеинурическое действие ингибиторов кальциневрина состоит в стабилизации актиново-го скелета подоцитов через их иммуномодулиру-ющий эффект на Т-клетки. Эта стратегия требует очень тщательного мониторинга их уровней [71,72]. В двух небольших проспективных исследова-ниях было описано использование такролимуса с преднизолоном [73,74].…”
Section: лечение стероидзависимых пациентов с фсгсunclassified
“…41 This strategy requires close monitoring of trough levels and kidney function. 42 The use of tacrolimus with prednisone has been described in two small prospective studies. 43,44 A Chinese trial compared the association of tacrolimus with prednisone to the association of IV cyclophosphamide with prednisone given to 33 adults with steroid-dependent or steroid-resistant FSGS: they reported 6-and 12-month cumulative remission rates of 67% and 73%, respectively, in the tacrolimus-prednisone group compared with 56% and 67%, respectively, in the cyclophosphamide-prednisone group.…”
Section: Treatment Of Steroid-dependent Nephrotic Syndrome In Patientmentioning
confidence: 99%